A Neonatal Intensive Care Unit’s Experience with Implementing an In-Situ Simulation and Debriefing Patient Safety Program in the Setting of a Quality Improvement Collaborative - Mary Eckels (Children, 2020)
Extensive neonatal resuscitation is a high acuity, low-frequency event accounting for approximately 1% of births. Neonatal resuscitation requires an interprofessional healthcare team to communicate and carry out tasks efficiently and effectively in a high adrenaline state. Implementing a neonatal patient safety simulation and debriefing program can help teams improve the behavioral, cognitive, and technical skills necessary to reduce morbidity and mortality. In Simulating Success, a 15-month quality improvement (QI) project, the Center for Advanced Pediatric and Perinatal Education (CAPE) and California Perinatal Quality Care Collaborative (CPQCC) provided outreach and training on neonatal simulation and debriefing fundamentals to individual teams, including community hospital settings, and assisted in implementing a sustainable program at each site. The primary Aim was to conduct two simulations a month, with a goal of 80% neonatal intensive care unit (NICU) staff participation in two simulations during the implementation phase. While the primary Aim was not achieved, in-situ simulations led to the identification of latent safety threats and improvement in system processes. This paper describes one unit’s QI collaborative experience implementing an in-situ neonatal simulation and debriefing program.